The Influence of Empowerment and Locus of Control on Job Satisfaction of Elementary School Teachers - Marlina Marlina; Daeng Ayub Natuna; Suarman Suarman (STAI Hubbulwathan Duri, 2022)
To better understand the impact of empowerment and locus of control on teachers' job satisfaction at State Elementary School, this study was conducted. Elementary school teachers were surveyed in the Bathin Solapan District of Bengkalis Regency in Indonesia. The Ex Post Facto model is used as a quantitative approach in the study. The Slovin formula was used to generate 67 samples from a population of a given size using proportional random sampling. In order to ensure the validity and reliability of a questionnaire, it was first tested in a controlled environment. Furthermore, multiple regression was used to analyze the data. According to the findings, both empowerment and locus of control had a positive and significant effect on teacher job satisfaction. And the two variables account for 68.3 % of the total, with the rest influenced by factors outside the scope of this investigation. They show a sense of responsibility for the assigned tasks by doing so. Teaching duties or work will be simple for teachers to help students achieve job satisfaction.